2018
DOI: 10.1177/1078155218818244
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Methylenetetrahydrofolate reductase C677T in younger acute lymphoblastic leukemia patients: A single-center experience

Abstract: Context: Methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms, mainly the C677T, have been implicated as risk factors for several cancers as the acute lymphoblastic leukemia (ALL). In addition, a potential effect of such variant on the efficacy of methotrexate (MTX) has been reported. Objective: In this study, we evaluated the impact of the C677T variant of MTHFR on MTX-related toxicity in ALL patients from Tunisia; to provide new insights for a personalized therapy based on the human genotype. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In fact; MTHFR C677T is often associated with MTX-HD toxicity and different types of toxicities have been reported. 13,14 The hepatotoxicity is the most commonly correlated adverse event to the C677T genotype, as reported by previous studies. 15…”
Section: Discussionsupporting
confidence: 66%
“…In fact; MTHFR C677T is often associated with MTX-HD toxicity and different types of toxicities have been reported. 13,14 The hepatotoxicity is the most commonly correlated adverse event to the C677T genotype, as reported by previous studies. 15…”
Section: Discussionsupporting
confidence: 66%
“…Multiple studies (n = 38) have studied the association between MTHFR c.677C > T and mucositis (den Hoed et al, 2015;Shimasaki et al, 2006;Liu et al, 2011;Aplenc et al, 2005;Faganel Kotnik et al, 2011;Karathanasis et al, 2011;Kishi et al, 2007;Lambrecht et al, 2017;Ongaro et al, 2009;Windsor et al, 2012;Xie et al, 2018;Xu et al, 2018;de Carvalho et al, 2018;Aráoz et al, 2015;Ayad et al, 2014;Eissa and Ahmed, 2013;Erculj et al, 2012Erculj et al, , 2014Frikha et al, 2019;Gemmati et al, 2007;Giletti et al, 2017;Haase et al, 2012;Huang et al, 2008;Jabeen et al, 2015;Mahmoud et al, 2018;Roy Moulik et al, 2015;Moulik et al, 2016;Pakakasama et al, 2007;Park and Shin, 2016;Radtke et al, 2013;Ramírez-Pacheco et al, 2016;Ruiz-Argüelles et al, 2007;Salazar et al, 2012;Seidemann et al, 2006;Suthandiram et al, 2014;Tantawy et al, 2010;Yazıcıoglu et al, 2017;Choi et al, 2017). In eight studies a statistically significant association was found (Faganel Kotnik et al, 2011;Ongaro et al, 2009;…”
Section: Mthfr C677c > T (Rs1801133)mentioning
confidence: 99%
“…There are conflicting results regarding the roles of the MTHFR gene polymorphisms in leukemia prognosis (5)(6)(7). Some studies have indicated that these variants play protective roles, whereas others have shown that they are linked to increased rates of relapse and drug resistance (1)(2)(3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme methylene tetrahydrofolate reductase (MTHFR) catalyzes the irreversible conversion of 5,10-methylene tetrahydrofolate to 5-methyl tetrahydrofolate, in the folic acid cycle, and is interrupted by MTX therapy. The pharmacokinetics and pharmacodynamics of this agent is known to be influenced, at least in part, by genetic variations (6,7). The most common MTHFR polymorphism C677T (are nonsynonymous amino acid changes) affect DOI: 10.51271/JTPM-0010 J Transl Pract Med 2022; 1(1): 9-13 MTHFR enzyme causing a reduction of its activity, altered distribution of intracellular folate metabolites and increased levels of blood homocysteine (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation